Gender Mainstreaming Problems in Student Organizations at Islamic Religious Colleges - Rr Rina Antasari; Nilawati Nilawati; Helen Sabera Adib; Renny Kurnia Sari; Dolla Sobari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze gender mainstreaming in student organizations from the basic aspects, student understanding, and policy implementation in several Islamic religious universities. This research is normative-empirical. This study found that implementing gender mainstreaming in student organizations was not optimal from the legal aspect, student understanding, and implementation. From the legal aspect, they have not included a philosophical foundation with the value of gender justice and equality, have not made a wise local academic culture the basis for sociological considerations, and have not included a juridical basis related to the acceleration of gender mainstreaming. From the aspect of student understanding of gender, it is still very low, which is indicated by the composition of the Intra-Campus Student Organization (OMIK) in strategic positions dominated by men. And from the aspect of implementation, it has not been optimal due to among others the commitment of the academic community to the enforcement of gender-responsive policies is still low and the activities in the field of student affairs that are carried out are not based on gender analysis.